Behavioral Analysis and Evaluation of Online Shoppers in the Philippines using the Proposed Online Shopping Website - Rodelas, Nelson C.; Rubio, Alexis John M.; Valdoz, Jherold John R.; Dimaano, Kathleen M.; Pasilan, Amelia A.; Dela Cruz, Edie Boy (International Journal of Computing Sciences Research, 2023)
Purpose – Online Shopping is proof that e-commerce is becoming more popular in the Philippines. There are so many online shopping sites and most of them were very popular not only here but also outside the country. The purpose of this study was to determine the behavioral analysis of consumers towards online shopping systems based on the online shopping practices and behavior of the customers. Method – The descriptive quantitative research approach was used in this study, with the questionnaire serving as the primary data collection tool. One hundred (100) respondents were chosen from a pool of business process outsourcing employees at a well-known corporation. Results – The many variables describing the respondents' online purchasing habit are classified into four categories: mall service availability, quality difficulties, and pricing concerns and interests. These practices may reflect respondents' attitudes toward internet buying. According to the findings, there is no significant association between the varied behaviors of the respondents and their demographic profile. This suggests that respondents' online buying behavior is unaffected by their age, gender, or financial level. Conclusion – It may be said that the Online Shopping System satisfies customers with the services, quality of the product, and reliable price offered by the system. Recommendations – This system contributes to the e-commerce popularity in the Philippines in line with the other common online websites. Implications – The inference is that customers' perceptions of a good deal and a worthwhile product or service are likely to impact online customer happiness directly. Then they should think about building methods to keep online clients, which means that the management should create not just a high-quality e-commerce infrastructure, but also excellent items, dependable delivery, and fair pricing.